2020
DOI: 10.1002/ansa.202000027
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of ring‐substituted regioisomers of cathinone analogs by supercritical fluid chromatography

Abstract: Various new psychoactive substances, such as cathinone and its analogs, possess similar chemical structures. Accurate identification of structurally similar drugs of abuse is important in forensic drug analysis. Chromatographic differentiation is a powerful analytical technique for this purpose. In this study, we applied supercritical fluid chromatography to differentiate ring-substituted regioisomers of six synthetic cathinone analogs (fluoro-𝛼-pyrrolidinovalerophenone, methyl-𝛼-pyrrolidinovalerophenone, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The results showed that polysaccharide‐based CSPs provide generally better enantioseparation and higher enantioselectivity for these liquid crystals compared to MG‐based CSPs. Other work compares enantioselective potential of TeicoShell and VancoShell columns for various groups of chiral analytes, that is, phytoalexins, ketamine, and cathinone derivatives, 76 substituted tryptophans, and calcium channel blockers. 74 The effect of co‐solvent type, that is, methanol, ethanol, propan‐2‐ol, and propan‐1‐ol on retention and enantioseparation were evaluated.…”
Section: Theoretical Studies Of Macrocyclic Glycopeptides In Sfcmentioning
confidence: 99%
“…The results showed that polysaccharide‐based CSPs provide generally better enantioseparation and higher enantioselectivity for these liquid crystals compared to MG‐based CSPs. Other work compares enantioselective potential of TeicoShell and VancoShell columns for various groups of chiral analytes, that is, phytoalexins, ketamine, and cathinone derivatives, 76 substituted tryptophans, and calcium channel blockers. 74 The effect of co‐solvent type, that is, methanol, ethanol, propan‐2‐ol, and propan‐1‐ol on retention and enantioseparation were evaluated.…”
Section: Theoretical Studies Of Macrocyclic Glycopeptides In Sfcmentioning
confidence: 99%